Combining Additive Manufacturing and Computational Fluid Dynamics to Optimize Scaffold Design: a Preliminary Study. (2019) - Bini, F.; Guachi, R.; Marconato, P.; Del Gaudio, C.; Marinozzi, F.
Abstract: The multidisciplinary field of tissue engineering and regenerative medicine can benefit from the potential of additive manufacturing as a fabrication technique that can realize custom medical devices. This is particularly true when referred to the macroscopic dimensions of the resulting scaffold, but focussing on the microstructure that should be realized to offer a suitable environment to the seeded cells, possible drawbacks can be highlighted. In this regard, the present study shows the design and validation of a custom-made set-up capable to deliver thin polymeric strands, below 100 µm diameter, to be used for building up scaffolds for tissue engineering applications. The aim of this work was to develop a specific experimental set-up capable of producing fine polymeric structures by means of a computer-controlled polymer deposition. As manufacturing method a variation of Pressure Assisted Microsyringe was chosen, namely the wet-spinning microsyringe deposition, driven by positive displacement as a trade-off between implementation complexity and extrusion speed control. For this purpose the project started with the design stage to select the proper hardware, especially for micro-positioning system's accuracy, then followed by a software development step to carefully control the setup. Experimental verification was carried out by depositing repeatable polymer filaments of poly(ε-caprolactone), widely used for tissue engineering applications. In order to preliminarily evaluate the feasibility of the desired outcome, a computational fluid dynamics analysis was carried out simulating a perfusion bioreactor operating at three different conditions. The results, either experimental and numerical, showed the potential of this combined study (i) to carefully select the most relevant processing parameters for collecting suitable strands and (ii) to predict the related response when assembled to form a 3D scaffold in terms of local fluid dynamics